Uma análise do modelo de propagação Longley-Rice sob aperspectiva de ambientes urbanos localizados em área de climatropical - Cristiano Torres do Amaral (2012)
Computer modeling of the propagation of radio frequency and signals an important tool for determining the coverage of radio and television around the world. This feature allows you to reduce deploymentcosts of broadcasting systems, which have the coverage previously evaluated in analytical studies for, at a later time, installation guide investment in infrastructure. Between different propagation models, theLongley-Rice model has emerged in 50 years to guide the installation of radio and television networks in the United States. Even today this model is used and considers attenuation parameters that depend onvariables related to climate, topography, among other features that have added their contribution to attenuate the signal received at one point or an area. However, these variables are different for each location, requiring a careful evaluation of each scenario and environment. Therefore, this paper presents a study on the contribution of the peculiarities of the state capital for formatting an attenuation factor-tropical city, adapting the U.S. model prediction for the Brazilian context, in particular, the state capital, which sent more efficiently analytical calculations to predict.